One health approach & COVID-19 for public health system strengthening: A literature review - Dewi, Kharisma (BKM Public Health and Community Medicine, 2021)
Objective: This study identified the importance and the benefits of one health approach for strengthening the public health system during the Covid-19 pandemic. Method: This research was done using a literature review from Google Scholar and PubMed. The journals chosen were recruited based on inclusion criteria using the keywords of “One Health” AND “Covid-19”. Results: The journals emphasized the importance of cross-sector collaboration. Human activities resulted in environmental changes such as deforestation and land-use shifts, forcing wildlife and their microorganisms to seek new hosts and triggering disease transmission, resulting in zoonoses disease. The coronavirus is known for its ability to mutate easily. There have been reports of disease transmission from human to animal. The first case was in the Bronx Zoo in New York, where two tigers and lions tested positive for SARS CoV-2. The transmission was traced back to their zookeeper, according to investigations. The Ragunan Zoo in Jakarta reported the first human-to-animal transmission in two tigers. The virus appears to be susceptible to the tiger and its family (Felidae). However, there had been no cats and their relatives (Felidae) to humans transmission reports until the writers completed this paper. Therefore, coordination and communication are needed to tackle and acknowledge the disease. These disease transmissions from animal to human, human to human, and human to animal (zoonotic) underlined the importance of surveillance between sectors under the same roof to strengthen the the public health system. Moreover, the One Health approach regained its recognition,, especially during the G-20 summit 2021 for the Ministry of Health meeting, as a resilience strategy in overcoming the next pandemic. One Health approach is considered suitable for preventing and combating the pandemic since experts in human, animal, and environmental health work together. Conclusions: One strategy to strengthen the public health system is establishing trust and collaborating across sectors for better public health outcomes. Since its integrity could manage developing public health challenges, one health is considered a great method of overcoming the pandemic.